2008
DOI: 10.1152/ajprenal.00449.2007
|View full text |Cite
|
Sign up to set email alerts
|

cGMP decreases surface NKCC2 levels in the thick ascending limb: role of phosphodiesterase 2 (PDE2)

Abstract: Ares GR, Caceres P, Alvarez-Leefmans FJ, Ortiz PA. cGMP decreases surface NKCC2 levels in the thick ascending limb: role of phosphodiesterase 2 (PDE2). Am J Physiol Renal Physiol 295: F877-F887, 2008. First published August 6, 2008 doi:10.1152/ajprenal.00449.2007.-NaCl absorption in the medullary thick ascending limb of the loop of Henle (THAL) is mediated by the apical Na/K/2Cl cotransporter (NKCC2). Hormones that increase cGMP, such as nitric oxide (NO) and natriuretic peptides, decrease NaCl absorption by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
91
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(97 citation statements)
references
References 40 publications
5
91
1
Order By: Relevance
“…Previous studies have reported that increases in cyclic guanosine monophosphate (cGMP) can decrease surface NKCC2 levels in the TALH acting through cGMP-stimulated phosphodiesterase 2. 23 Because HO-1 induction has been shown to increase cGMP levels through generation of CO, 24 it is possible that induction of HO-1 in TALH cells attenuates NKCC2 through CO-mediated increases in cGMP, resulting in increased degradation of the protein. However, measurement of NKCC2 protein in the apical membrane of the TALH in TALH-HHO1 mice by surface biotinylation was not determined and is needed to fully test this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that increases in cyclic guanosine monophosphate (cGMP) can decrease surface NKCC2 levels in the TALH acting through cGMP-stimulated phosphodiesterase 2. 23 Because HO-1 induction has been shown to increase cGMP levels through generation of CO, 24 it is possible that induction of HO-1 in TALH cells attenuates NKCC2 through CO-mediated increases in cGMP, resulting in increased degradation of the protein. However, measurement of NKCC2 protein in the apical membrane of the TALH in TALH-HHO1 mice by surface biotinylation was not determined and is needed to fully test this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…THAL suspensions were also obtained from another group of HS and HS ϩ HCTZ-treated SS rats. Medullary THAL suspensions were prepared according to the method described previously (2,5,27). In brief, kidneys were perfused via the aorta with a perfusion solution (in mM: 130 NaCl, 2.5 NaH 2PO4, 4.0 KCl, 1.2 MgSO 4, 6 L-alanine, 1.0 disodium citrate, 5.5 glucose, 2.0 calcium lactate, and 10 HEPES, pH 7.4) containing 0.1% collagenase (Sigma, St. Louis, MO) and 100 U heparin.…”
Section: Methodsmentioning
confidence: 99%
“…Cell surface proteins were biotinylated as described in detail previously (2,5,27). THAL suspensions were equilibrated at 37°C for 20 min and oxygenated every 5 min with 100% O 2 with gentle mixing every 2 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations